2018
DOI: 10.1144/jgs2017-150
|View full text |Cite
|
Sign up to set email alerts
|

A continental record of the Carnian Pluvial Episode (CPE) from the Mercia Mudstone Group (UK): palynology and climatic implications

Abstract: The generally arid Late Triassic climate was interrupted by a wet phase during the mid Carnian termed Carnian Pluvial Episode (CPE). Quantitative palynological data from the Mercia Mudstone Group in the Wessex Basin (UK), reveals vegetation changes and palaeoclimate trends. Palynostratigraphy and bulk organic carbon isotope data enable 9 Laxitexella multireticulata within the Lincombe Member in the coastal sections which is indicative of the early Carnian L. mucroreticulata Zone (Kozur & Weems 2010). This spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 93 publications
3
35
0
Order By: Relevance
“…This is an extremely interesting finding. Indeed, a second negative carbon isotope excursion within the Julian 2 has been recently found also in organic carbon from marine sections of northwestern Tethys realm (Italy and Hungary), and in successions from continental Pangea (Miller et al 2017;Baranyi et al 2018;Dal Corso et al 2018b), as well as in carbonate carbon from a marine succession in Southwest China (Sun et al 2016). During the Carnian Oman was located c. 30°S, and these new data from the southern hemisphere add a precious tessera in our understanding of Carnian carbon cycle changes.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…This is an extremely interesting finding. Indeed, a second negative carbon isotope excursion within the Julian 2 has been recently found also in organic carbon from marine sections of northwestern Tethys realm (Italy and Hungary), and in successions from continental Pangea (Miller et al 2017;Baranyi et al 2018;Dal Corso et al 2018b), as well as in carbonate carbon from a marine succession in Southwest China (Sun et al 2016). During the Carnian Oman was located c. 30°S, and these new data from the southern hemisphere add a precious tessera in our understanding of Carnian carbon cycle changes.…”
mentioning
confidence: 75%
“…Franz et al documented a clear deviation of the clay chemistry and type of palaeosols in the Shilfsandstein with respect to previous and subsequent units of the Central European Basin that could be explained, however, without changes of rainfall. This work should be compared with Barrenechea et al (2018), Lucas & Tanner (2018) and Baranyi et al (2018), who studied similar continental successions and found evidence for climate change, albeit less intense than suggested by Simms & Ruffell (1989) and recorded in most marginal marine successions of Tethys. The debate is still open.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…alluvial sheet sandstones, evaporite pseudomorphs, tepees and sulphates) recognized in sheet sandstone facies. This culminated in deposition of the widespread, and relatively thicker, fluvial sands of the Arden Sandstone Formation and its wider correlatives that form a key line of evidence for the Carnian Pluvial Episode, a period of globally enhanced precipitation (Simms & Ruffell, ; Ruffell et al ., ; Baranyi et al ., , ).…”
Section: Discussion: Dryland Mudstone Facies Developmentmentioning
confidence: 99%